Effect of thymoquinone on cyclophosphamide-induced oxidative and inflammatory ovarian damage in rat - Cagdas Colluoglu; Serdar Balci; Betul Gundogdu; Taha Abdulkadir Coban; Seval Bulut; Halis Suleyman (Bangladesh Pharmacological Society, 2022)
This study intends to investigate the effect of thymoquinone against possible ovarian damage and infertility caused by cyclophosphamide in female rats. The rats in the experiment (n=36) were separated into three groups; cyclophosphamide administered, thymoquinone plus cyclophosphamide administered and healthy control. At the end of 30 days of administration, 6 rats from each group were killed and the biochemical and histopathological examina-tions were performed on the ovarian tissues. The remaining animals were kept in the same cage with mature male rats for two months. Infertility developed in 83% of cyclophosphamide group animals. Thymoquinone attenuated cyclophosphamide-related oxidative and inflammatory ovarian damage and reduced the development of infertility. The outcomes suggest that thymoquinone may be useful in treating infertility due to oxidative and inflammatory ovarian damage.